Innovative Controlled-Release Systems for Fucoxanthin: Research Progress and Applications - Shiyan Wang; Mengran Guo; Zhaohui Jin (Pharmaceutics, 2025)
Fucoxanthin, a marine-derived carotenoid primarily sourced from algae and microalgae, holds significant potential for pharmaceutical and nutraceutical applications. However, its highly unsaturated structure presents critical challenges, including structural instability, poor aqueous solubility, and limited bioavailability. These restrict its application despite its abundant natural availability. Recently, various controlled-release nanotechnologies have been applied to improve the properties of fucoxanthin formulations. In this review, we systematically summarized the bioactivities of fucoxanthin and highlighted recent advancements in controlled-release systems designed to address the limitations. These controlled-release systems mainly use natural or synthetic organic materials and are employed to develop various formulations, including emulsions, nanoparticles, nanofibers, and nanostructured lipid carriers. In addition, the emerging bioinspired drug delivery systems, particularly extracellular vesicles and cell-membrane-derived biomimetic systems, have gained prominence for their immunocompatibility and ability to penetrate physiological barriers, which is regarded as superior encapsulation vesicles for fucoxanthin. Focusing on innovations, we discussed the state-of-the-art delivery systems for fucoxanthin encapsulation and emphasized their roles in improving biosafety, enhancing bioavailability, preserving bioactivity, and optimizing therapeutic performance across various disease models. These insights will provide promising guidance for engineering controlled-release platforms and will aim to unlock fucoxanthin’s full potential in drug development and dietary supplement formulations.